New earwigs of the subfamily Anechurinae (Dermaptera: Forficulidae) from China - Chen, Zhi-Teng (Zootaxa, 2024)
The species-rich earwig family Forficulidae remains relatively understudied in China. This study reports a new species of Chelidura Latreille, 1825 (Forficulidae: Anechurinae), Chelidura siguniangshana sp. nov., from central Sichuan Province of China, and provides detailed descriptions and illustrations. Notable characteristics of the new Chelidura species include slender and medially straight forceps, shallow lateral tubercles on the ultimate tergite, elongated genitalia, and slender, asymmetrical parameres in males. In addition, Parachelidura liui gen. et sp. nov. is described based on a male specimen also found in Sichuan Province. The new genus is distinguished by the complete absence of tegmina and wings, coupled with a robust molar-tooth in the basal quarter of the male forceps.